Etika Komunikasi Qur’ani dalam Menghadapi Polarisasi Sosial: Kajian Tematik atas Ayat-Ayat Qaul dalam Al-Qur’an - Haidar Idris (Moderasi : Journal of Islamic Studies, 2025)
Social polarization has become one of the most critical issues in contemporary public communication, particularly in digital spaces marked by misinformation, hate speech, prejudice, verbal aggression, and identity-based conflict. This article examines the ethical principles of Qur’anic communication embedded in the qaul verses and constructs them as a normative-conceptual framework for mitigating social polarization. This study employs a qualitative library research design using a thematic-contextual exegetical method. The primary corpus consists of Qur’anic verses containing the formulations qaulan sadīdan, qaulan ma‘rūfan, qaulan balīghan, qaulan karīman, qaulan maysūran, and qaulan layyinan. The data were analyzed through verse identification, classification of communicative contexts, examination of classical and contemporary Qur’anic exegesis, and contextualization of their ethical meanings in relation to contemporary problems of social communication. The findings reveal that the Qur’an establishes an ethics of communication through six core principles: truthfulness, civility, dialogical gentleness, transformative effectiveness, respect for human dignity, and inclusive communication that promotes reassurance and social harmony. These principles can function as an ethical framework for countering disinformation, reducing verbal aggression, preventing dehumanization, protecting vulnerable groups, and opening spaces for dialogue and reconciliation. This article contributes to Qur’anic exegesis, Islamic studies, and communication ethics by shifting the interpretation of the qaul verses from a merely normative description toward a contextual framework for addressing contemporary social fragmentation.